Visual Transformation of Gender Representation on The Famous Five: Five on a Treasure Island Book Covers (1942-2017) - Imaduddin, Farid; Murtono, Taufik (Westscience Press, 2025)
This study examines the visual transformation of gender representation on the covers of Enid Blyton's